Effects of stereoscopic 3D display technology on event-related potentials (ERPs) - Amin, H.U. (IEEE Computer Society, 2015)
The purpose of this study is to explore the effects of stereoscopic 3D (S3D) display technology on event-related brain potentials (ERPs). A sample of thirty-four healthy participants was subjected to an oddball paradigm after being exposed to stereoscopic 3D contents with passive polarized display or traditional 2D display. The participants were randomly assigned to two groups - 2D group and S3D group; in such a way that their intelligence ability and age were controlled between the groups. The behavioral and ERP results did not show any significant differences between S3D and 2D groups for either ERP components (amplitude and latency) or accuracy and response time of the target detection. These results suggest that passive polarized S3D display technology may not induce any effects (cognitive or visual fatigue) which may disturb the ERP components. Â© 2015 IEEE.